Transforming Structural Breakdown into Sensory Perception of Texture. Issue 3 (5th March 2015) - Foegeding, E. Allen; Vinyard, Christopher J.; Essick, Gregory; Guest, Steve; Campbell, Caroline
Abstract Food structure research has historically focused on building and stabilizing specific structural elements. Precise execution of unit operations in food processing is required to ensure consistent structure formation, but does not explain why a particular structure is desirable. The pattern by which food structure breaks down during oral processing, generating texture, flavor and taste, determines the acceptability of a food. However, breakdown patterns and textural perception associated with desirable food qualities are not well understood. Food materials are classified based on their physical state (liquids, semisolids or solids) and interactions with surfaces (adhesive or nonadhesive). Physical and chemical processes during oral processing are used to further characterize each food category. Typical processes include particle reduction, dissolution, hydration, removal of food from oral surface and bolus formation. This review presents a framework for classifying food materials and material transformations during oral processing in order to identify their contributions to texture perception. Practical Applications There is a constant desire to reformulate or modify foods based on economic, sustainability, health and dietary considerations. One goal of a reformulated food is to change the composition but cause no significant changes in flavor, taste and textural properties associated with desirability. An alternative goal is to modulate a specific textural element to make the food more acceptable to a target population (e.g., those with compromised chewing ability). Both goals require an understanding of the fundamental elements that cause specific textural properties. This manuscript presents an overview of how the breakdown of food structure during oral processing generates the cognition of textural properties. Once textural properties are understood based on specific elements of structural transitions, this will allow for development of textures for specific market segments (e.g., vegan, gluten free or swallowing disorders) as well as the ability to control nutrient bioavailability and flavor release.